Debriphor in Chronic Ulcers - N. N. Khanna; A. Kumar; S. Khanna (Indian Journal of Plastic Surgery)
Debriphor, a dextran polymer has absorbent properties. In the present study twenty patients of chronic ulcers in adults have been treated with this substance with good results.